Assessing Resident Confidence in Placing a Central Venous Catheter Before and After a Simulation-Based Training Course (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Internal Medicine; Research